Grand Designs handbook the blueprint for building your dream home - McCloud, Kevin 1959- (Collins, 2006)
TV's architecture and design guru Kevin McCloud shares his passion and expertise in this brilliant guide to designing and building your own home, illustrated with the most memorable houses from the award-winning Channel 4 series